2018
DOI: 10.1016/j.celrep.2018.04.115
|View full text |Cite
|
Sign up to set email alerts
|

A Non-canonical Feedback Circuit for Rapid Interactions between Somatosensory Cortices

Abstract: SUMMARYSensory perception depends on interactions among cortical areas. These interactions are mediated by canonical patterns of connectivity in which higher areas send feedback projections to lower areas via neurons in superficial and deep layers. Here, we probed the circuit basis of interactions among two areas critical for touch perception in mice, whisker primary (wS1) and secondary (wS2) somatosensory cortices. Neurons in layer 4 of wS2 (S2L4) formed a major feedback pathway to wS1. Feedback from wS2 to w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
69
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(81 citation statements)
references
References 70 publications
10
69
2
Order By: Relevance
“…At the population level (n = 9 mice), responses in S2 presented an overall small but significant delay in latency (+3.3 +/− 1.2 ms, Fig. 3b2,b3), consistently with recently reported electrophysiological data 8 . Although the amplitude of evoked responses was smaller in S2 than in S1 for the illustrated case ( Fig.…”
Section: Comparison Of Whisker-evoked Responses In S2 and S1 Quantifsupporting
confidence: 90%
See 2 more Smart Citations
“…At the population level (n = 9 mice), responses in S2 presented an overall small but significant delay in latency (+3.3 +/− 1.2 ms, Fig. 3b2,b3), consistently with recently reported electrophysiological data 8 . Although the amplitude of evoked responses was smaller in S2 than in S1 for the illustrated case ( Fig.…”
Section: Comparison Of Whisker-evoked Responses In S2 and S1 Quantifsupporting
confidence: 90%
“…Each neuronal column associated with a barrel receives primarily the input coming from its corresponding whisker. Upon tactile stimulation of a given whisker, information is indeed rapidly transmitted to its corresponding barrel in S1, but also, within the next couple of milliseconds, to the secondary somatosensory cortex S2 [5][6][7][8] . The rapid activation of S2 neurons following whisker stimulation is likely to rely on the direct projections it receives from both the ventral posteromedial nucleus [9][10][11] and the posteromedial complex of the thalamus [12][13][14] .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, our study provides a direct anatomical comparison of these three long-range projections. The overall laminar distributions of POm, M1, and S2 projections to barrel cortex here are consistent with previous observations of the individual projections (Kinnischtzke et al, 2014;Minamisawa et al, 2018;Ohno et al, 2012;Veinante and Deschenes, 2003;Wimmer et al, 2010). We found that these three areas differ in their infragranular targets.…”
Section: Discussionsupporting
confidence: 92%
“…Infarct volumes were calculated using ImageJ by measuring the largest area of the infarct in all 4 coronal sections, which was normalised by the ratio of ipsilesional to contralesional cortical volumes 5 to exclude the shift effect of cortex. 6 7 In vivo electrophysiological recording 8 Electrophysiological recordings were performed at postoperative day 3 (POD3) and POD14, which 9 correspond to the acute and subacute phases of the infarction, respectively (Fig. 1).…”
Section: Photothrombotic Infarction In Mouse Vm1mentioning
confidence: 99%